TANAMAN TARUM ( Indigofera tinctoria Linn. ) SEBAGAI PENGHASIL ZAT PEWARNA - Mira Ariyanti; Yenni Asbur (JURNAL HUTAN PULAU-PULAU KECIL, 2018)
Indonesia is known as a country with high biodiversity in the world. Plenty of beneficial-rich plants grow in Indonesia as a country that has tropical climate, one of the plant is tarum (Indigofera tinctoria Linn.). Tarum is a natural dye-producing plant whose presence is not widely known. The development of human needs, especially in meeting the needs of natural dyes, is considered to be the main reason for reintroducing tarum as a suitable plant to grow in Indonesia. The use of natural dyes in addition to being safe for humans is also safe for the environment, considering the substances produced by the tarum plant are widely used as textile dyes. Good enough environmental compatibility makes this plant actually spread in many parts of Indonesia, especially in Java. It is necessary to possess a knowledge about the right cultivation techniques for tarum plants in an effort to increase the color-producing substances in plants. The attempts to obtain information about cultivation techniques are an opportunity to re-raise these plants to be better known and developed as potential plants.